Morphological Features of Mosquito Larvicidal Bacillus Thuringiensis Isolated From Soil Samples of Nepal - GC, Ganga; Banjara, Megha Raj; Gautam, Ishan; Ghimire, Prakash; Rijal, Komal Raj (Tribhuvan University Journal, 2023)
Anopheles, Culex, and Aedes spp are the main vectors for transmitting malaria, Japanese encephalitis, lymphatics filariasis, dengue, zika, chikungunya, etc. Mosquito-borne diseases are increasing especially dengue in Nepal. Additional tools are required to decrease the disease rate. Biological control tools like Gambusia fish, Cyclopods, Bacillus thuringiensis, etc., have not been adopted and are unavailable in Nepal. The research aims to isolate mosquitocidal Bacillus thuringiensis a biological control tool from the soil samples of Nepal. Bacillus thuringiensis (Bt) was isolated from the soil samples of Nepal by the acetate selection method. The larvicidal bioassay of Bt was studied against the field-collected mosquito larvae. The isolate showing larvicidal activity was coded as Bacillus thuringiensis -14P2A (Bt-14P2A). The growth pattern of the positive control strain Bacillus thuringiensis var israelensis (Bti-IPS-82) and the test strain were studied in different types of culture media. The microscopic morphology was studied by using different staining techniques. Bt-14P2A and Bti -IPS-82 caused 100% mortality of field-collected larvae. Both the strains showed the same type of colony morphology in a standard culture media and uniform turbidity with sedimentation type of growth pattern in broth media. The strains were Gram-positive single rod-shaped of size 1.2X4.8µm in both negatively stained slides and Gram-stained slides. A slight difference in the endospore location was terminal in Bti-IPS-82 and subterminal in Bt-14P2A. The newly isolated Bt-14P2A differs from Bti-IPS-82 in arrangement and endospore location but harbors the same morphological characteristic and larvicidal activity as the positive control strain.